Naegleria fowleri outbreak in Pakistan: unveiling the crisis and path to recovery - Nadeem, Abdullah; Malik, Inshal Arshad; Afridi, Eesha Khan; Shariq, Fariha (Frontiers in Public Health, 2023)
The outbreak of Naegleria fowleri in Pakistan presents a significant public health concern due to its high fatality rate and limited treatment options. This review explores the impact of the outbreak on communities and the challenges faced in combating the disease. It evaluates available treatment options and highlights the need for early diagnosis and intervention. The study proposes recommendations to improve public health preparedness, including public awareness campaigns, enhanced healthcare infrastructure, and robust water surveillance systems. Collaboration between research institutions and public health organizations is emphasized to develop effective outbreak response strategies.